2019
DOI: 10.9744/ced.21.2.97-106
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Vulnerability Maps of Ratu Agung District, Bengkulu City, Indonesia

Abstract: During the 8.6 Mw Bengkulu-Mentawai Earthquake Ratu Agung District was identified as an impacted area. This paper aims to deliver the seismic vulnerability based on geophysical observation. This study was initiated by performing the ambient noise measurement to obtain the geophysical characteristic, such as amplification and predominant frequency. Furthermore, the vulnerability index analysis was performed from the geophysical information collected from the investigation. To observe the tendency of ground dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Generally, the results of this study are relatively consistent with the study of Mase (2019), who investigated the geophysical characteristic of subsoils in Ratu Agung District, including Lempuing Subdistrict. Mase (2019) implemented the horizontal to vertical spectral ratio (HVSR) technique suggested by Nakamura (1989), to investigate the goophysical characteristic of Ratu Agung District. Based on geophysical investigation performed Mase (2019), areas in Lempuing Subdistrict are dominated by sandy soils.…”
Section: Map Of Lsimentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the results of this study are relatively consistent with the study of Mase (2019), who investigated the geophysical characteristic of subsoils in Ratu Agung District, including Lempuing Subdistrict. Mase (2019) implemented the horizontal to vertical spectral ratio (HVSR) technique suggested by Nakamura (1989), to investigate the goophysical characteristic of Ratu Agung District. Based on geophysical investigation performed Mase (2019), areas in Lempuing Subdistrict are dominated by sandy soils.…”
Section: Map Of Lsimentioning
confidence: 99%
“…Mase (2019) implemented the horizontal to vertical spectral ratio (HVSR) technique suggested by Nakamura (1989), to investigate the goophysical characteristic of Ratu Agung District. Based on geophysical investigation performed Mase (2019), areas in Lempuing Subdistrict are dominated by sandy soils. Mase (2019) also confirmed the report of Hausler and Anderson (2007) who mentioned that liquefaction was found on Lempuing Subdistrict.…”
Section: Map Of Lsimentioning
confidence: 99%
“…It is therefore very useful to be implemented in the area with high seismic intensity, such as Bengkulu City, Indonesia (Mase, 2019). This paper presents a seismic microzonation study.…”
Section: Introductionmentioning
confidence: 99%
“…Mase et al (2020) suggested that V s30 is the important parameter to describe seismic vulnerability in an area. It is therefore very useful to be implemented in the area with high seismic intensity, such as Bengkulu City, Indonesia (Mase, 2019).…”
Section: Introductionmentioning
confidence: 99%